PERILAKU PENGENDARA OJEK (STUDI KASUS DI PERUMAHAN GADING MARPOYAN KECAMATAN BUKIT RAYA KOTA PEKANBARU) - Putri Mayang Sari; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at Perumahan Gading Marpoyan Kecamatan Bukit Raya Kota Pekanbaru. The purpose of this research is to analyze the behavior of motorbike rider at Perumahan Gading Marpoyan Kecamatan Bukit Raya Kota Pekanbaru. The main focus in this study is the behavior of motorcycle traffic at Perumahan Gading Marpoyan Kecamatan Bukit Raya Kota Pekanbaru. The sample in this study amounted to 5 people. The author uses descriptive and qualitative methods of data are analyzed qualitatively and using purposive sampling technique. Data instruments are observations, in-depth interviews and documentation. From the research conducted, the authors found that the behavior of motorbike riders in traffic and serve the passengers are as follows :1. Precautions, In observing alertness, research subjects always pay attention to personal health and self condition so as not to bring bad impact for passengers. 2. Awareness, to pay attention to consciousness, passengers with the usual remember the nature of his work not only about the fulfillment of economic needs itself. 3. Anticipate, in increasing the quantity of work, motorbike rider need to pay attention to the condition of the body which must always be healthy and fit. Factors that influence motorbike rider behavior in traffic and serving passengers are as follows : Internal factors (Motivation, knowledge, skill, age and economy) and External factors (vehicle condition and environmental conditions).Keywords: Behavior, Behavior Factor, Motorbike Rider